(3TQM GdTeSjIs - (3GdJGaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J (B793 (3g`s
(3ChdgG (B:s
... (3GdJUOjbGJ hGdJUhQ ebOe Ydi GdJUOjb WHYG adjbOe Ydjg hUaG djhGab GdhVY GdWHY hEfeG bdfG GdJUhQ ebOe Ydi GdJUOjb WHYG dCf GdJbOe GdWHjYj gh Gf jchf GdeJbOe HMjK jMJGL Edjg GdeJCNQ hdG jchf YdI dg cGdhGMO HGdfSHI ddGKfjf (B...s
(3BNQgG (B:s
.. (3bGd hbO LQJ GdYGOI ; Cbhd (B: (3hbO YQaJ Cf GdZQV ef GdefWb GSJMUGd GdeLghdGJ hGdeLghd EeG JUhQj Ch JUOjbj afXQ GdefWbj EeG aj GdehUd Edi GdJUhQ hEeG aj GdehUd Edi GdJUOjb hbO LQJ YGOI GdefWbjjf Cf jSehG GdehUd (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\ 219s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdadSaI hGdefWbs